1988
DOI: 10.1073/pnas.85.7.2269
|View full text |Cite
|
Sign up to set email alerts
|

Alloreactive immune responses of transgenic mice expressing a foreign transplantation antigen in a soluble form.

Abstract: Transfection of cells with the H-2Kk gene lacking the transmembrane and cytoplasmic segments resulted in secretion of the H-2Kk protein, as determined by immunoprecipitation with monoclonal anti-H-2Kk antibodies. Transgenic (H-2b x H-2d)Fj mice were established carrying integrated copies of the modified H-2Kk gene. Expression of the soluble H-2Kk antigen in the transgenic mice was demonstrated in cell supernatants of biosynthetically labeled splenic and thymic Con A blasts as well as bone marrow-derived macrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

1988
1988
1994
1994

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(22 citation statements)
references
References 24 publications
0
22
0
Order By: Relevance
“…We have recently reported that transgenic mice expressing a foreign class I antigen in soluble form could still react with the same high frequency of CTL precursors to the membranebound alloantigen as normal mice (8). We could, however, not exclude that the lack of tolerance toward the membrane antigen was based on the fact that the concentration of the antigenic protein in the serum (200 ng/ml) might have been insufficient to induce any tolerance.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…We have recently reported that transgenic mice expressing a foreign class I antigen in soluble form could still react with the same high frequency of CTL precursors to the membranebound alloantigen as normal mice (8). We could, however, not exclude that the lack of tolerance toward the membrane antigen was based on the fact that the concentration of the antigenic protein in the serum (200 ng/ml) might have been insufficient to induce any tolerance.…”
Section: Discussionmentioning
confidence: 66%
“…Soluble H-2Kk was present in the sera of the transgenic animals (200 ng/ml). In spite of this, the transgenic mice were able to generate H-2Kk-specific CTL responses when stimulated with cell membrane-bound H-2Kk antigens (8). We have now analyzed the CTL responses of these animals to soluble H-2Kk by using either cells or recombinant vaccinia virus expressing soluble H-2Kk for immunization.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These results were expected but needed to be verified because in some transgenic systems lack of tolerance was observed. For example, not all mice transgenic for the simian virus 40 large tumor antigen were tolerant due to late expression during ontogeny (33), and transgenic mice expressing soluble H-2 antigens were not tolerant in their respective CTL and antibody compartments (34).…”
Section: Discussionmentioning
confidence: 99%
“…In such situations, the B cell appears simply to ignore the antigen and no tolerance develops. Examples include transgenic foreign MHC deprived of its transmembrane domain [49], transgenic human insulin in the mouse [SO] and low concentrations of transgenic hen egg lysozyme (HEL) [32]. In those examples no B cell tolerance develops, although T cell tolerance may do so, presumably through passage of the protein concerned into the thymus, followed by local processing and presentation leading to clonal abortion.…”
Section: Clonal Abortion and Clonal Anergy In B Lymphocyte Tolerancementioning
confidence: 99%